STRATEGIES OF SOCIALLY RESPONSIBLE MARKETING OF COMPANIES IN THE SPHERE OF SPORTS - Marcel Kurt Mainka; Oksana Melnichenko; Artem Tsybrovskyi; Danylo Sidielnikov; Vitalii Nitsenko; Serhii Zakharin (Фінансово-кредитна діяльність: проблеми теорії та практики, 2023)
The main goal of the research is to study and evaluate modern socially responsible marketing strategies of global sports brands for the development of proposals for the domestic sports business. The article examines the role and significance of the social responsibility of business in modern marketing strategies of companies. The essence of socially responsible marketing and types of marketing strategies have been studied. The key marketing strategies that are relevant under modern market conditions are distinguished. It was determined that charity, sponsorship, and active participation in environmental protection programs are the most popular forms of social responsibility of sports companies. The largest and most popular sports companies were chosen on the basis of the rating evaluation results of the world's sports brands. According to the official websites of the world's leading sports companies, the content of strategic marketing initiatives that take place in their management practice was analyzed. It was found that all global sports brands have a high level of activity in the field of social responsibility of business. Among the most popular marketing strategies, these companies use the production of goods from ecological raw materials, the strategy of transformational cyclicality and energy efficiency, the promotion of a healthy lifestyle among potential and contact audiences, the involvement of consumers in programs for the preservation and restoration of natural resources, the observance of human rights, the strategy of inclusiveness and equality for all categories of consumers. Studies of the Ukrainian market of sports brands have shown that many new companies have appeared in the country in recent years, however, their level of social business responsibility remains low compared to global sports brands. In order to create favourable conditions for the success of Ukrainian sports companies on the basis of the best global practice, strategic areas of socially responsible marketing were proposed. The main elements of marketing strategies were identified as key elements of the implementation of these strategic initiatives, including reputational capital and branding, active promotion technologies based on digital potential, socially significant long-term values, unity of business interests and the interests of society.